Pengaruh Kompensasi, Pelatihan dan Pengembangan Serta Budaya Organisasi Terhadap Retensi Karyawan Dengan Kepuasan Kerja Sebagai Mediasi Pada Industri Perbankan Swasta di Kota Batam - Nelson, Alden; Viona, Viona (Universitas Islam Kadiri, 2024)
Employee retention is a company strategy to retain employees to stay with the company for a certain period of time. Banking companies that are successful in providing good training and development programs, appropriate compensation and a comfortable and harmonious organizational culture will certainly increase job satisfaction which is in line with employee retention levels. This research was conducted to determine the impact of compensation, training and development and organizational culture on employee retention. In this research, job satisfaction is a mediating variable. The population studied were all employees who actively worked in the private banking industry in Batam City. This research used quantitative research and obtained 280 respondents. Data analysis uses the Structural Equation Modeling (SEM)-SmartPLS method. The data collection method used was a questionnaire distributed online via Google Form. The results of this research are that compensation, training and development and organizational culture have a positive and significant impact on employee retention with job satisfaction as mediation. Keywords: Compensation, Training and Development, Organizational Culture, Employee Retention, Job Satisfaction